2020
DOI: 10.1101/2020.04.15.20063107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between ABO blood groups and clinical outcome of coronavirus disease 2019: Evidence from two cohorts

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become the third most common coronavirus that causes large-scale infections worldwide. The correlations between pathogen susceptibility and blood type distribution have attracted attention decades ago. The current retrospective study aimed to examine the correlation between blood type distribution and SARS-CoV-2 infection, progression, and prognosis in patients with coronavirus disease 2019 . With 265 patients from multiple medical centers and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 31 publications
6
68
0
1
Order By: Relevance
“…The frequency of blood group A in COVID-19 patients was significantly higher compared to the non-COVID-19 group. In a study conducted by Zeng et al (10), 35% of the patients with mild pneumonia and 39% of the patients with severe pneumonia had blood group A. These patients had a higher frequency of blood group A compared to the general population.…”
Section: Discussionmentioning
confidence: 94%
“…The frequency of blood group A in COVID-19 patients was significantly higher compared to the non-COVID-19 group. In a study conducted by Zeng et al (10), 35% of the patients with mild pneumonia and 39% of the patients with severe pneumonia had blood group A. These patients had a higher frequency of blood group A compared to the general population.…”
Section: Discussionmentioning
confidence: 94%
“…In the first study by Zeng et al has reported in their preprint that their retrospective study examined 265 COVID-19 patients from multiple medical centres and two established cohorts, where they found that the blood type A population was more sensitive to SARS-CoV-2. 29 Their findings are indicative of coping with the great threat since it probed the relationship between blood types and ARDS, acute kidney injury, and mortality, in addition to susceptibility in COVID-19 patients. 29 In another independent GWAS study by an Italian and a Spanish group, Ellinghaus et al which included 1,600 COVID-19 patients in hotspot cities in Italy and Spain has also shown that those with blood group A were at a higher risk while those with O were protected to some degree.…”
Section: Abo Blood Groups Are Associated With Susceptibility To Develmentioning
confidence: 99%
“…29 Their findings are indicative of coping with the great threat since it probed the relationship between blood types and ARDS, acute kidney injury, and mortality, in addition to susceptibility in COVID-19 patients. 29 In another independent GWAS study by an Italian and a Spanish group, Ellinghaus et al which included 1,600 COVID-19 patients in hotspot cities in Italy and Spain has also shown that those with blood group A were at a higher risk while those with O were protected to some degree. 30 They have discovered at least a couple of significant associations, including one that located at the ABO blood group locus.…”
Section: Abo Blood Groups Are Associated With Susceptibility To Develmentioning
confidence: 99%
“…In another study from China, a report by Zeng et al comparing a cohort of COVID-19 patients with mild symptoms to another with severe symptoms, showed higher proportions of patients with blood group A in both groups (36% and 39% respectively), compared to a reference population, confirming that individuals with blood group type A were more susceptible to COVID-19 infection. [6] The calculated OD was 1.40 (95% CI:…”
Section: Introductionmentioning
confidence: 99%